The Process of Industrial Design as a Tool for Business Management - Arroyo, Flavio (2020)
Industrial design is a valuable tool that companies can implement in their favour, unfortunately there are few who are aware that for the emergence of them, innovation should be developed through design for both products and services, by disseminating the Technologies, shortening the life cycle of products and business strategies that refer to the need to meet demands, that is, to identify opportunities based on strategic models that reinforce the competitiveness of companies, not forgetting the importance of innovation Of products, systems or services that handle environmentally friendly strategies, taking into account the implementation of the circular economy, which favors companies in their finances. Then the continuous adaptation and modification of your products through all means mentioned above will help to maintain your position or gain advantages over your competitors.